Application of Features of Virtual Curriculum Components of Virtual Courses in Medical Sciences - Seyyed Mohsen Azizi; Mehran Farajollahi, Farhad Seraji; Alireza Khatony; Mohammad Reza Sarmadi (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objective: With regard to the quantitative expansion of virtual education in universities of medical sciences, the quality and coordination of curriculum with features of virtual education environment must be considered. Therefore, this study aimed to evaluate the application of features of virtual curriculum components in virtual education courses in medical sciences. Materials and Methods: This descriptive and cross sectional study was conducted on all virtual MSc students of Tehran and Shahid Beheshti Universities of Medical Sciences, Iran. Sample size was estimated at 140 using Cochran sample size formula, and subjects were selected by stratified random sampling. Data were collected using a researcher-made questionnaire, the validity of which was evaluated and confirmed using CVA and CVR indexes. In addition, the reliability of the research tool was estimated at the Cronbach's alpha of 0.77. Moreover, data analysis was performed in SPSS version 19 using one sample t-test. Results: In this study, the mean features of objective, content, role of e-instructor and assessment components in the virtual courses in medical sciences was at a relatively realized level (2.33-3.66). Conclusion: Curriculum designers and specialists can review the curriculum design of virtual courses in medical sciences based on the features of the virtual curriculum components.